2022
DOI: 10.3389/fpsyt.2022.830383
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Lifestyle on Insomnia in Home Quarantine College Students During the COVID-19 Epidemic

Abstract: There has been sufficient evidence for the relationship between lifestyle and insomnia in the general population, but for individuals who already suffer from insomnia, it is not clear whether a healthy lifestyle can also pose similar benefits. The present study investigated the roles of different aspects of lifestyle in the development of individual insomnia by tracking insomnia symptoms of college students during the COVID-19 lock-down. Two surveys were conducted on 65,200 college students in the process of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Low glycemic index could be one of the characteristics of fruits and vegetables with high fiber content that contribute to reducing insomnia symptoms [ 26 ]. In addition, as important constituents of an anti-inflammatory diet, eating fruits and vegetables in high intakes may help improve insomnia symptoms and sleep quality by promoting production of melatonin and other neurotransmitters including onset and maintenance of sleep, together with restoring the circadian rhythm of the master biological clock [ 77 79 ]. These mechanisms could be responsible for the findings that higher FV may be beneficial to sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Low glycemic index could be one of the characteristics of fruits and vegetables with high fiber content that contribute to reducing insomnia symptoms [ 26 ]. In addition, as important constituents of an anti-inflammatory diet, eating fruits and vegetables in high intakes may help improve insomnia symptoms and sleep quality by promoting production of melatonin and other neurotransmitters including onset and maintenance of sleep, together with restoring the circadian rhythm of the master biological clock [ 77 79 ]. These mechanisms could be responsible for the findings that higher FV may be beneficial to sleep.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhang et al posited that routine physical exercise serves as a protective factor against the occurrence of chronic insomnia. 14 Hurdiel et al revealed that college students engaging in regular physical activity exhibit a notably lower incidence of sleep disturbances compared to their counterparts without such routines. 53 The facilitation of enhanced sleep quality through physical activity can be elucidated from several perspectives.…”
Section: Physical Activity and Sleep Qualitymentioning
confidence: 99%
“…12 A 19-day longitudinal study also demonstrated that less physical activity carries a higher risk of chronic insomnia. 14 Nevertheless, prior research has predominantly concentrated on the nexus between physical activity and sleep quality, leaving the potential mediating mechanisms (ie, how physical activity exerts influence on sleep quality) considerably unexplored during the COVID-19 period. Furthermore, although the relationship between individual characteristics such as depression, 15 anxiety, 16 and loneliness 17 and sleep quality has been extensively discussed in prior studies, the parallel psychological states of stress and smartphone addiction as factors affecting sleep quality have been relatively understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the study was designed to examine the relationship between lifestyle and insomnia from the perspective of the dynamic evolution of sleep problems. Insomnia exerts non-negligible adverse effects on an individual's daily life (Zhang, 2022). It was reported that insomnia impairs physical and mental functions, reduces work productivity, and could also cause mental problems, such as anxiety and depression, and even suicide.…”
Section: Review Of Literaturementioning
confidence: 99%